Microbial Colonization and Inflammation as Potential Contributors to the Lack of Therapeutic Success in Oral Squamous Cell Carcinoma - Kurago, Zoya; Loveless, Jenni (Frontiers in Oral Health, 2021)
This review discusses the microenvironment of evolving and established conventional oral squamous cell carcinoma, by far the most common oral cancer. The focus of this paper is mainly on the more recent data that describe the role of microorganisms, host-microbial interactions, and in particular, the contributions of cell-surface toll-like receptors on immune system cells and on normal and malignant epithelial cells to their functions that support carcinogenesis. Because carcinomas arising at various host surfaces share much in common, additional information available from studies of other carcinomas is included in the discussion. Accumulating evidence reveals the complex toll-like receptor-mediated pro-tumor input into many aspects of carcinogenesis via malignant cells, stromal immune cells and non-immune cells, complicating the search for effective treatments.